Diorhabda lusca, Maulik (Coleoptera : Chrysomelidae), a Serious Pest of Celtis australis in Low and Mid-hills of Himachal Pradesh - Sharma, Ajay; Verma, T. D.; Sood, Anil (Indian Forester, 2007)
Celtis australis Linn. leaves are damaged severely by the larvae and adults of Diorhabda lusca Maulik. These brown coloured beetles started appearing in the last week of March with the new flush of leaves. In a period of 8 months i.e. from March to October, the insect completed 4 generations and the adults of the 4th generation underwent hibernation to resume the activity in next March. The biology, nature and extent of damage is presented in this paper.